Cloud computing: issues and challenges - Dillon, Tharam S.; Wu, Chen; Chang, Elizabeth (IEEE Computer Society, 2010)
Knowledge would be considered as important element in knowledge-based economy and it makes a strong competitive advantage in dynamic business environment. In knowledge management, knowledge sharing is the most critical elements of effective knowledge processing. Several studies have been done to explain why people share knowledge and some of them have been mentioned in this paper. The next issue is how knowledge sharing can be improved and how it can be measured. Different models from different view points such as social and psychological aspect or economic benefit aspect have been proposed to analyse and measure knowledge sharing effectiveness. In this paper, we will review some of the main models in knowledge sharing effectiveness and will explain a new method to measure knowledge sharing effectiveness among individuals.